2021
DOI: 10.1111/jan.14853
|View full text |Cite
|
Sign up to set email alerts
|

The experiences of nurses and midwives who provide surgical abortion care: A qualitative systematic review

Abstract: Aim To synthesize qualitative evidence on nurses' and midwives' experiences in the provision of surgical abortion care. We address three specific questions: (a) what are the experiences of nurses and midwives in surgical abortion care? (b) what are their responses and coping strategies? (c) what are the deficiencies in surgical abortion care? Design Qualitative studies were synthesized using Thomas and Harden's qualitative thematic synthesis method. Data sources Electronic databases, including PubMed, Embase, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 63 publications
2
18
0
Order By: Relevance
“…It is necessary to add personnel and provide equal care to all women. Burnout, emotional exhaustion and other negative emotions among healthcare staff may lead to reduced quality of care [ 17 ], and sufficient emotional support should be offered to relieve their emotional labour [ 50 ]. There is a need for employee assistance programmes, including group psychological interventions and meditation, to relieve negative moods [ 27 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is necessary to add personnel and provide equal care to all women. Burnout, emotional exhaustion and other negative emotions among healthcare staff may lead to reduced quality of care [ 17 ], and sufficient emotional support should be offered to relieve their emotional labour [ 50 ]. There is a need for employee assistance programmes, including group psychological interventions and meditation, to relieve negative moods [ 27 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, the knowledge and skills of PTSD management should be improved by providing training to healthcare professionals. On the other hand, there is a need to establish a communication platform to provide adequate psychological and professional support for providers 22. Comprehensive PTSD symptom-reducing interventions based on these three core components could be referred in clinical implementation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that a stressful work environment and lack of sufficient organisational support could be antecedents of PTSD 11 15. Healthcare professionals described their experiences of trauma and PTSD as feeling alone and unsupported and lacking emotional support 21 22. This may lead to adverse consequences among healthcare professionals, such as burnout, job dissatisfaction and the intention to leave their job 15.…”
Section: Introductionmentioning
confidence: 99%
“…Third, we are concerned that the SM/DBT regimen finds more cancers: 7.2/1000 for SM/ DBT vs. 6.3/1000 for DM/DBT, and 5.5/1000 for DM alone (Zheng et al 2021). The rate of invasive breast cancer is very low and has remained unchanged in recent decades: 94% of women will remain free of invasive cancer after 25 years of follow-up (Cutler et al, 2020;Welch et al, 2017).…”
Section: Bringing Home the Bacon And The Breastmilkmentioning
confidence: 99%